Evaluasi Perkembangan Literasi Menulis melalui Analisis Logiko-Semantik: Studi Perbandingan Teks Argumentatif di Sekolah dan Perguruan Tinggi - Moh. Rizchald Walidain; Wawan Gunawan (Journal on Education, 2024)
This study aims to examine the development of students' writing literacy across educational levels. The research questions to be answered are: 1) How does writing literacy, in terms of logico-semantic aspects, develop in argumentative texts between high school students and university students? And 2) Are there significant differences in the logico-semantic structure of argumentative texts between high school students and university students? The method used is a comparative study with high school students and university students as subjects. Data in the form of argumentative paragraph texts were collected and analyzed using logico-semantic analysis, which involves the identification and assessment of the structure and logical relationships between clauses. The results of the study indicate a significant development of writing literacy from high school students to university students, marked by an increase in complexity and variation in the use of logico-semantic relations. University students' texts show better argument quality and coherence. This study suggests the need for systematic development of argumentative writing instruction from school to university, with a focus on strengthening text structure, logic, use of evidence, and more complex use of logico-semantic relations.